Midtrophic fish feeding modes at the poles: an ecomorphological comparison of polar cod (Boreogadus saida) and Antarctic silverfish (Pleuragramma antarctica) - Carlig E.; Christiansen J. S.; Di Blasi D.; Ferrando S.; Pisano E.; Vacchi M.; O'Driscoll R. L.; Ghigliotti L. (Polar Biology, 2021)
The polar cod (Boreogadus saida) and the Antarctic silverfish (Pleuragramma antarctica) are pelagic fish endemic to the Arctic and Antarctica sea, respectively. Both species are abundant and play a central role as midtrophic wasp-waist species in polar ecosystems. Due to their biological and ecological characteristics (small size, complex life histories, relatively short generation cycles, movement capability, planktivorous diet, and importance as prey), the polar cod and the Antarctic silverfish are potentially good sentinels of ecosystem change. Changes in polar zooplankton communities are well documented. How changes impact ecosystems as a whole largely depend on the degree of diet specialization and feeding flexibility of midtrophic species. Here, we provide the ecomorphological characterization of polar cod and Antarctic silverfish feeding performances. A comparative functional ecology approach, based on the analysis of morpho-anatomical traits, including calculation of suction index and mechanical advantage in jaw closing, was applied to profile the feeding modes and flexibility of the two species. Ecomorphological evidence supports differences in food acquisition: the polar cod appears able to alternate particulate ram-suction feeding to a pump filter feeding, and the Antarctic silverfish results be both a particulate ram and a tow-net filter feeder. Both species exhibit opportunistic feeding strategies and appear able to switch feeding mode according to the abundance and size of the available prey, which is a clue of potential resilience to a changing environment.